Criminal Policy for Users Ofservices Prostitution to Achieve Substantial Justice - Chumairo, Maryamul; Masyithoh, Novita Dewi; Adila, Arina Hukmu (Universitas Islam Negeri Walisongo Semarang, 2021)
Prostitution is a form of sexual deviation and disease of society and also against Indonesian morality. Therefore, its existence is a problem for the Indonesian nation. One of the causes is that criminal formulation policies are set within KUHP specifically article 296 jo. article 506 only discussing about criminal responsibility for a pimp. The other parties involved in such prostitution as prostitutes (sex workers) and client of prostitutes are not convicted unless one or both are committed in marriage, so it can be convicted under article 284 which qualifies for a felony in adultery. Based on these issues, this research aims to learn and analyze criminal policy for client of prostitutes in positive laws in Indonesia and criminal policy for client of prostitutes to realize substantial justice. The results of this research show that criminal policy for client of prostitutes in positive laws is not optimal. The arrangement of prostitution in particular article 296 jo. 506 KUHP only disscuss about criminal resonsibility for a pimp, so there is a legal vacuum in Indonesia's penal formulation policy that regulates prostitution. The government's policy to close brothels in Indonesia still raises problems as it is not followed by reformulation of criminal laws that regulate prostitution crimes. Thus, it has been necessary for criminal policy either by penal or non-penal efforts to realize the laws expected by society and to attain substantial justice (the perfect justice). The author's recommendation would be to include new legal norms governing prostitution crimes and encourage governments to legitimize RUU KUHP and RUU PKS.[]Praktik prostitusi ini menjadi problematika tersendiri bagi bangsa Indonesia. Salah satu penyebabnya adalah rumusan pemidanaan yang diatur dalam KUHP khususnya Pasal 296 jo. Pasal 506 hanya berkaitan dengan pertanggungjawaban pidana muncikari. Pihak lain seperti pekerja seks komersial dan pengguna jasa prostitusi tidak dimintai pertangungjawaban, kecuali bila salah satu terikat hubungan perkawinan (Pasal 284 KUHP). Penelitian ini ditujukan untuk mengetahui dan menganalisis mengenai kebijakan kriminal bagi pengguna jasa prostitusi dalam hukum positif di Indonesia dan kebijakan kriminal bagi pengguna jasa prostitusi yang berkeadilan substansial. Hasil penelitian menunjukkan bahwa criminal bagi pengguna jasa prostitusi dalam hukum positif Indonesia belum optimal. Pengaturan mengenai prostitusi khususnya dalam Pasal 296 jo. Pasal 506 KUHP hanya berkaitan dengan pertanggungjawaban pidana bagi muncikari (hal ini didasarkan karena KUHP/WvS masih dipengaruhi budaya hukum Belanda dan Prancis), sehingga menimbulkan adanya kekosongan hukum dalam kebijakan formulasi hukum pidana di Indonesia yang mengatur terkait praktik prostitusi. Upaya non penal melalui penutupan lokalisasi juga masih menyisakan permasalahan karena tidak diikuti dengan reformulasi hukum pidana yang mengatur terkait kejahatan prostitusi. Oleh karenanya, dibutuhkan kebijakan kriminal baik melalui pendekatan penal maupun non penal yang berkeadilan substansial untuk mewujudkan keadilan yang dicita-citakan masyarakat. Adapun rekomendasi penulis adalah dengan memasukkan norma hukum baru yang mengatur mengenai kejahatan prostitusi dan mendorong pengesahan RUU KUHP dan RUU PKS.